An evaluation of northern bobwhite translocation to restore populations. Issue 5 (19th March 2017) - Downey, Michelle C.; Rollins, Dale; Hernández, Fidel; Wester, David B.; Grahmann, Eric D.
ABSTRACT: Northern bobwhite ( Colinus virginianus) populations have been declining in Texas during the last 2 decades. This decline also is occurring in areas with apparently ample habitat such as the Rolling Plains of Texas, USA. The goal of our study was to examine the efficacy of translocating wild‐trapped bobwhites into recently depopulated areas in the eastern Rolling Plains as a method of restoring population size. Our objectives were to document survival (spring‐summer and annual), reproductive efforts, and site fidelity of translocated bobwhites and compare relative abundance of bobwhites between release and control sites to evaluate the efficacy of translocation. We translocated 409 wild bobwhites ( n = 186 radio‐marked F) to 2 sites in Shackelford and Stephens counties, Texas, during March 2013 and 2014. Spring‐summer (Mar–Sep) survival ranged between 0.32 and 0.38 ( n = 186 bobwhites), and annual survival ranged between 0.19 and 0.23 ( n = 186 bobwhites) during 2013–2015. Seventy‐four percent of translocated females that entered the nesting season (i.e., May 1; n = 112 bobwhites) produced a nest, resulting in 125 nests with an apparent nest success of 46.1% and a nesting rate of 1.1 ± 0.1 (SE) nests/female. Site fidelity post‐translocation was moderate to high; 67.7% ( n = 44 bobwhites) and 85.1% ( n = 40 bobwhites) of translocated bobwhites did not disperse >2 km from their release point during the summers of 2013 and 2014, respectively. Despite this strong demographic performance, relative abundance of bobwhites did not differ between the release and control sites after 2 years as indexed by covey‐call counts (2.7 ± 0.6 vs. 3.0 ± 1.2 coveys/point, respectively; P = 0.71) and helicopter surveys (0.9 ± 0.2 vs. 0.7 ± 0.2 bobwhites/km, respectively; P = 0.64). Thus, translocation of bobwhites failed to increase the bobwhite population beyond that of the control during this study. Future translocation research should aim to increase translocation success by investigating methods for increasing survival during the 1‐month period following translocation (e.g., soft‐release, vitamin E and selenium injections) and for improving site fidelity using conspecific attraction. Future research should incorporate genetic measures to assess genetic contribution of translocated individuals to improve evaluation of translocation success. © 2017 The Wildlife Society. Abstract : We documented survival, reproductive effort, and site fidelity of translocated northern bobwhites and compared bobwhite relative abundance between release and control sites to evaluate the efficacy of translocation. Despite a strong demographic performance (high annual survival, high reproductive effort, and moderate site fidelity) by translocated bobwhites, we did not document a population response resulting from translocation of wild bobwhites beyond that of the control.